2018
DOI: 10.1371/journal.pone.0204154
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the lethal and sublethal effects by spinetoram on cotton bollworm

Abstract: Helicoverpa armigera is an universal pest around the world, which has recovered again in recent years because of the adjustment of cropping structure and resistance to Bacillus thuringiensis (Bt) in China. As a new insecticide spinetoram is extensively used to control many pest insects, including H. armigera. However the lethal and sublethal effects of spinetoram on cotton bollworm have not been assessed. In the present study, the toxicity of spinetoram against cotton bollworm was tested under laboratory condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…Insecticide resistance in Lepidopteran is a major concern throughout the world because several species of it have been reported to have developed resistance to several classes of insecticides Wei et al (2018). The present study revealed high levels of resistance to profenofos and cyfluthrin in the tested field population; at the same time, emamectin benzoate, spinetoram, and lufenuron showed low levels of resistance.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Insecticide resistance in Lepidopteran is a major concern throughout the world because several species of it have been reported to have developed resistance to several classes of insecticides Wei et al (2018). The present study revealed high levels of resistance to profenofos and cyfluthrin in the tested field population; at the same time, emamectin benzoate, spinetoram, and lufenuron showed low levels of resistance.…”
Section: Discussionsupporting
confidence: 48%
“…Therefore, it was necessary to study the effect of some new insecticides that appeared in the Egyptian market on S. littoralis, in terms of their toxicity and their effect on enzymes that plays a defensive role in changing the response to insecticide in S. littoralis becomes extremely tolerant of the action of insecticides because of the intensive treatments of these insecticides. Therefore, new insecticides with modes of action that differed from conventional insecticide are highly desirable in integrated pest management (IPM) programs among these insecticides are insect growth regulators (IGRs), avermectin, and spinosyn insecticide group (Subramanian and Shankarganesh, 2016;Wei et al, 2018). Different mechanisms of resistance to organophosphate and pyrethroid insecticides have been identified in S. littoralis, including enhanced metabolism, nerve insensitivity, reduced penetration, and target site insensitivity; it is caused by defensive enzymes in the insect (Rong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…has increased in recent years. Spinetoram has been reported to have high efficacy against Helicoverpa species under field conditions [67,68]. Interestingly, spinosad resistance is associated with a reduced fitness, as reflected in prolonged egg, larval, and pupal periods and decreased pupal survival and overall fecundity [66].…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that spinetoram is highly toxic to both Helicoverpa species. This insecticide is considered an important alternative for controlling Helicoverpa pests, especially for Cry1Ac-resistant populations [68]. Xie et al [67] found spinetoram to be effective against H. armigera, inducing high mortality rates and sublethal effects similar to spinosad in H. armigera populations from China [66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation